Skeletal muscle wasting in chronic kidney disease: the emerging role of microRNAs - Robinson, Kate A; Baker, Luke A; Graham-Brown, Matthew P M; Watson, Emma L (Nephrology, dialysis, transplantation, 2020)
Skeletal muscle wasting is a common complication of chronic kidney disease (CKD), characterized by the loss of muscle mass, strength and function, which significantly increases the risk of morbidity and mortality in this population. Numerous complications associated with declining renal function and lifestyle activate catabolic pathways and impair muscle regeneration, resulting in substantial protein wasting. Evidence suggests that increasing skeletal muscle mass improves outcomes in CKD, making this a clinically important research focus. Despite extensive research, the pathogenesis of skeletal muscle wasting is not completely understood. It is widely recognized that microRNAs (miRNAs), a family of short non-coding RNAs, are pivotal in the regulation of skeletal muscle homoeostasis, with significant roles in regulating muscle growth, regeneration and metabolism. The abnormal expression of miRNAs in skeletal muscle during disease has been well described in cellular and animal models of muscle atrophy, and in recent years, the involvement of miRNAs in the regulation of muscle atrophy in CKD has been demonstrated. As this exciting field evolves, there is emerging evidence for the involvement of miRNAs in a beneficial crosstalk system between skeletal muscle and other organs that may potentially limit the progression of CKD. In this article, we describe the pathophysiological mechanisms of muscle wasting and explore the contribution of miRNAs to the development of muscle wasting in CKD. We also discuss advances in our understanding of miRNAs in muscle–organ crosstalk and summarize miRNA-based therapeutics currently in clinical trials.